2015
DOI: 10.3109/0142159x.2015.1044956
|View full text |Cite
|
Sign up to set email alerts
|

Exploring digital professionalism

Abstract: The widespread use of digital media (both computing devices and the services they access) has blurred the boundaries between our personal and professional lives. Contemporary students are the last to remember a time before the widespread use of the Internet and they will be the first to practice in a largely e-health environment. This article explores concepts of digital professionalism and their place in contemporary medical education, and proposes a series of principles of digital professionalism to guide te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 15 publications
0
57
0
8
Order By: Relevance
“…Como alternativa para uma formação mais abrangente, que possa ampliar a visão da ética, pode ser interessante incluir, na graduação médica, docentes formados em Ciências Sociais e Ciências Humanas, como sugerido por Gomes e colaboradores 33 no artigo "O lugar da Ética e Bioética nos currículos de formação médica". Alguns estudos evidenciaram que intervenções educacionais em profissionalismo on-line podem gerar maior senso de responsabilidade e comprometimento de estudantes e médi-cos nas redes sociais [34][35][36][37] . Além disso, esses estudos sugerem a inclusão da abordagem do profissionalismo no meio digital e on-line na educação médica [34][35][36][37] .…”
Section: Discussionunclassified
“…Como alternativa para uma formação mais abrangente, que possa ampliar a visão da ética, pode ser interessante incluir, na graduação médica, docentes formados em Ciências Sociais e Ciências Humanas, como sugerido por Gomes e colaboradores 33 no artigo "O lugar da Ética e Bioética nos currículos de formação médica". Alguns estudos evidenciaram que intervenções educacionais em profissionalismo on-line podem gerar maior senso de responsabilidade e comprometimento de estudantes e médi-cos nas redes sociais [34][35][36][37] . Além disso, esses estudos sugerem a inclusão da abordagem do profissionalismo no meio digital e on-line na educação médica [34][35][36][37] .…”
Section: Discussionunclassified
“…Although 26% of respondents indicated that no current social media sites were suitable for study purposes, the validity of utilising digital media to enhance professional education cannot be discounted. As stated in previous studies, negative consequences of the use of digital media can be avoided by effective planning of the integration of digital media for educational purposes [12].…”
Section: The Nexus Of Social Media and Higher Educationmentioning
confidence: 92%
“…Development of digital professionalism during their undergraduate program, and at graduation is necessary to ensure health profession students understand the need for safe and appropriate use of digital technologies while in the workplace [12]. The inception of a University social media policy [3] at this University has enabled modelling of appropriate behaviour to be included in curricula and implemented in on-campus classes [23,24] prior to students going into the workplace as a consequence of these policy developments.…”
Section: Digital Professionalismmentioning
confidence: 99%
See 1 more Smart Citation
“…5 As much as we might question the relevance of using an EHR for residency training, there is another, perhaps larger, issue: the use of syntactic log data to monitor how health professionals use EHRs and other e-health technologies. Tracking and monitoring are key aspects of Internet technologies, 6 and Chen et al have illustrated this power by using the logs of individual residents' clicks and keystrokes to make inferences about their behaviors and the value of those behaviors. 4 It should be noted that Chen et al are not the only researchers to use log data to make inferences about clinical behaviors; 7 there seems to be a growing acceptance of this approach.…”
mentioning
confidence: 99%